Patient safety risk associated with synchronous telehealth: A scoping review - Juliana Salomão Rocha de Oliveira; Rafael Saad Fernandez; Mônica Rossatti Molina; Ana Carolina P.N. Pinto; César Ramos Rocha-Filho; Tiago M. Ferreira; Stela Verzinhasse Peres (PLoS ONE, 2025)
Objective We aimed to analyze the risks associated with patient safety in synchronous telehealth. Methods Scoping review with search in 3 databases, Medical Literature Analysis and Retrieval System Online (Medline), via PubMed®, Embase® via Elsevier®, and the Cochrane Database of Systematic Reviews, recovering evidence from inception until September 4 th , 2024. Eligible reviews investigated patient safety concerns arising from real-time interactions between healthcare professionals and patients through information and communication technologies (ICT), including telephones and videoconferencing tools. We included systematic reviews examining real-time telehealth interactions between healthcare professionals and patients, addressing safety concerns. We followed standard Joanna Briggs Institute methods for conducting the scoping review. Results A total of 3,641 titles and abstracts were retrieved, and after screening, 15 systematic reviews were included, encompassing 315 studies. These reviews addressed various patient populations, healthcare settings, and telehealth interventions, including virtual consultations, telepharmacy, and telerehabilitation. All 15 reviews reported patient safety risks associated with telehealth, the most frequently reported concern was the patient’s experience, highlighted in 53.3% (n = 8) of the included studies. Additional concerns involved user knowledge gaps and the lack of safety criteria in evaluation protocols. These risks were categorized into five domains: patient experience, safety in prescribing medication, effective communication, training and education, and patient identification. Conclusion This scoping review provides evidence that, although telehealth offers valuable alternatives for healthcare delivery, all evidence highlights specific patient safety risks that require attention. Further research is essential to better understand and mitigate these risks. Strategic investments in education, training, and structured implementation are critical to minimizing adverse events and enhancing patient safety in synchronous telehealth.